This is why we pay—Motivational factors for supporting subscription-based crowdfunding campaigns - Hendrik Jöntgen; Nicholas Valentin Lingnau; Oliver Hinz; Roland Holten (Electronic Markets, 2024)
Abstract Subscription-based crowdfunding platforms emerged as novel digital platforms that offer creators the possibility of financial independence. They differ significantly from traditional time-limited crowdfunding approaches by utilizing recurring payments and enabling a creator-centric rather than campaign-centric funding approach. We built upon previous research on individuals' motivation to support crowdfunding campaigns, and utilizing self-determination theory, our study explores which subscription-based crowdfunding campaign characteristics influence individuals' motivation to support them. We use a two-method approach by analyzing individual pledge data from a subscription-based crowdfunding platform and conducting a discrete choice experiment. Our results show that having a high number of previous supporters increases potential supporters' willingness to pay, while a campaign's current recurring income and the hiding of this piece of information decrease it. We could also identify a u-shaped effect of campaigns' goal proximity on willingness to pay. We discuss the theoretical and practical contributions of our research and provide an overview of potential future research directions.
Additional information: D26;D9;D90;D91;G11;G23;G4;G40;G41
Keywords: 330; Crowdfunding; Subscription; Motivation; Digital platforms and ecosystems; Quantitative research